Patrology : v. 4. The golden age of Latin patristic literature from the Council of Nicea to the Council of Chalcedon - Quasten, Johannes, 1900-; Di Berardino, Angelo (Westminster, Md. : Christian Classics, Inc., 1986)
Angelo di Berardino, with an introduction by Johannes Quasten
translation from the Italian
Keywords: Patristics (3Yde GdBHGFjGJs; Christian literature, Early -- History and criticism; History; Fathers of the church -- Criticism and interpretation